Deep structure of South Kamchatka according to geophysical data - Yu. F. Moroz; L. I. Gontovaya (Геодинамика и тектонофизика)
Differences have been discovered in the deep structures of North and South Kamchatka, which raises a question about a boundary between these regions. This problem has been studied on the basis of the seismologic, inverse seismic tomographic (P-waves) and geoelectrical data obtained in recent years, as well as the information on magnetometry, gravimetry, tectonics and magmatism of the study area. Comprehensive analysis of the geological and geophysical data shows differences in the structure of the crust and upper mantle in North and South Kamchatka and common features of the deep structures of South Kamchatka and the Kuril Islands. A presumed boundary between North and South Kamchatka is related to the zone of transverse deep faults crossing the peninsula. It is evidenced by P-wave velocity anomalies at different levels of the lithosphere. This fault zone is associated with a change in the geometry and strike of the high-velocity focal layer, and reflected in the modern tectonic plan as the Petropavlovsk-Malkinsky zone of transverse dislocations. In this zone, the Avacha-Koryak group of modern volcanoes is also NW-oriented. We propose a geoelectric model showing the depths along the profile constructed across the zone. In its deep part, the model includes sub-vertical anomalies of increased electrical conductivity. The anomalies are related to deep faults. Increased electrical conductivity may be due to the presence of magmatic melts feeding volcanoes. The results obtained in our study give evidence of the common features of the deep structures of South Kamchatka and the Kuril island arc and demonstrate the differences between the deep structures of North and South Kamchatka, being separated by the zone of faults, which may penetrate into the upper mantle. It is suggested that the identified features in the South Kamchatka structure are due to deep processes taking place not only at the side of the Pacific Ocean, but also at the southern margins of the Sea of Okhotsk. These findings are of interest for geodynamics, volcanology, tectonics and other Earth sciences.